2016
DOI: 10.1111/1750-3841.13544
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intestinal Microbiota on the Catabolism of Flavonoids in Mice

Abstract: Although in vitro studies have shown that flavonoids are metabolized into phenolic acids by the gut microbiota, the biotransformation of flavonoids by intestinal microbiota is seldom studied in vivo. In this study, we investigated the impact of the gut microbiota on the biotransformation of 3 subclasses of flavonoids (flavonols, flavones, and flavanones). The ability of intestinal microbiota to convert flavonoids was confirmed with an in vitro fermentation model using mouse gut microflora. Simultaneously, puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 43 publications
1
55
1
Order By: Relevance
“…Moreover, it has been hypothesized that oxidative stress could enhance inflammation in IBD and colitis-associated colon cancer through impaired S1P degradation [2]. Protocatechuic acid (PCA, 3-4-dihydroxybenzoic acid) is a simple phenolic acid found in many edible vegetables, fruits and nuts [9], which has been identified as a major metabolite of complex polyphenols and considered the best biomarker of flavonoid consumption [10,11]. A number of cellular and animal studies have shown that PCA has multifaceted biological effects, including a potent antioxidant and anti-inflammatory activity, in different tissues [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been hypothesized that oxidative stress could enhance inflammation in IBD and colitis-associated colon cancer through impaired S1P degradation [2]. Protocatechuic acid (PCA, 3-4-dihydroxybenzoic acid) is a simple phenolic acid found in many edible vegetables, fruits and nuts [9], which has been identified as a major metabolite of complex polyphenols and considered the best biomarker of flavonoid consumption [10,11]. A number of cellular and animal studies have shown that PCA has multifaceted biological effects, including a potent antioxidant and anti-inflammatory activity, in different tissues [9].…”
Section: Introductionmentioning
confidence: 99%
“…The significant role of gastrointestinal (GI) microflora in digestion, absorption, health, productivity and other physiological functions has been well recognized (Pourabedin and Zhao, 2015), moreover the intestinal microflora may also protect hosts from pathogens (Waite and Taylor, 2014) and inflammatory bowel diseases to improve gut health (Giacomin et al, 2016); also Lin et al (2016) studied that intestinal microbiota were necessary for transformation of flavonoids to provide health benefits for the prevention and treatment of some types of chronic diseases. Therefore, it is very relevant to assay the composition of the GI microflora (Barbosa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The colonic microflora also reduces cholesterol absorption and increases mucus secretion in the gut [162, 163]. The role of the colonic microflora on the absorption, metabolism, and bioavailability of flavonoids remains to be delineated [164]. It has been reported that unabsorbed flavonoids can be biotransformed to small phenolic compounds that have similar effects, but improved bioavailability, compared to the parent compound [165].…”
Section: Challenges In Flavonoids In Cancer Chemoprevention Developmentmentioning
confidence: 99%
“…It has been reported that unabsorbed flavonoids can be biotransformed to small phenolic compounds that have similar effects, but improved bioavailability, compared to the parent compound [165]. In contrast, the colonic microflora can extensively metabolize (via cleaving the heterocycle break) flavonoids via the enzymes glucuronidase and sulphatase, producing metabolites that are primarily inert polar compounds that are rapidly excreted [164, 166168]. Some flavonoids (e.g., apigenin, genistein, naringenin, and kaempferol) are more likely to undergo microflora degradation compared with others, resulting in lower bioavailability [169].…”
Section: Challenges In Flavonoids In Cancer Chemoprevention Developmentmentioning
confidence: 99%